Effectiveness Of Problem-Based Learning And Discovery Learning To Cognitive Learning Results On Cell Subject Of Senior High School Students - Sushariyanti Sushariyanti; Didimus Tanah Boleng; Lambang Subagiyo (Universitas Negeri Malang, 2020)
Abstract: The learning process is strived to be able to improve cognitive learning outcomes. The cognitive learning outcomes of students of  XIth class students majoring in natural sciences in city of Samarinda, are still low. Quasi-experimental studies have been conducted in XIth class majoring in natural science, odd semester of 2017/2018 academic year. The aim of the research is to determine the effect of implementation of Problem-Based Learning and Discovery Learning models on student's cognitive learning outcomes. The study sample is students of XIth class majoring in natural sciences in 1st public senior high schools. The sampling technique is pusposive sampling. Instruments of study  are test questions. The data were analyzed using ANCOVA. The data analysis result show that the sign value is 0.00; this means 0.00 < 0.05 (p < 0.05). The conclusion is the implementation of learning models affect student's cognitive learning outcomes. Further studies are needed by enlarging the sample to obtain more information. Abstrak: Proses pembelajaran diupayakan untuk dapat meningkatkan hasil belajar kognitif. Hasil belajar kognitif siswa kelas XI jurusan ilmu pengetahuan alam di kota Samarinda masih rendah. Penelitian kuasi eksperimental ini telah dilaksanakan di kelas XI jurusan IPA semester ganjil tahun ajaran 2017/2018. Tujuan penelitian ini adalah untuk mengetahui pengaruh penerapan model Problem Based Learning dan Discovery Learning terhadap hasil belajar kognitif siswa. Sampel penelitian adalah siswa kelas XI jurusan IPA SMA Negeri 1. Teknik pengambilan sampel adalah pusposive sampling. Instrumen penelitian adalah soal tes. Data penelitian dianalisis menggunakan ANCOVA. Hasil analisis data menunjukkan bahwa nilai signifijkansi adalah sebesar 0,00; ini berarti 0,00 < 0,05 (p < 0,05). Penelitian ini menyimpulkan bahwa penerapan model pembelajaran berpengaruh terhadap hasil belajar kognitif siswa. Diperlukan penelitian lebih lanjut dengan memperbesar sampel untuk mendapatkan informasi lebih lanjut.